USE OF E-FILLING AND E-FORM AS A MEASURE OF WPOP AND WP AGENCY COMPLIANCE - Wulandari Ansori; Rusmida Jun Hutabarat; Yuni Rachmawati (Jurnal Manajemen, 2024)
This study aims to find out and analyze how taxpayers comply in reporting annual tax returns using e-filing and e-form at KPP Pratama Seberang Ulu Palembang. This study used quantitative descriptive data analysis techniques. The source of data used in this study is secondary data in the form of the number of individual and corporate taxpayers who report annual tax returns at KPP Sebrang Ulu Palembang. The data collection technique used in this study is documentation. The population in this study is the number of compliance of individual taxpayers and entities who have filed annual tax returns at KPP Pratama Sebrang Ulu Palembang after the implementation of e-filing and e-form until now. The sample in this study is the amount of compliance of individual and corporate taxpayers who report Annual Tax Returns at KPP Sebrang Ulu Palembang for 2018-2023 using a saturated sampling method. The results showed that the use of e-filling for individual taxpayers is less effective and for corporate taxpayers is not effective while the use of e-form is very ineffective for individual and corporate taxpayers